Vattenjärnhaltens betydelse för mjölkkors hälsa och produktion - Olofsson, Helena (2006)
Drinking water from drilled wells has a high content of iron and other minerals in many places in Sweden. Questions about the association between the quality of drinking water and the health of dairy cows are regulary asked both by advisers and dairy farmers. There are so far not many studies published about the relevance for high iron content in water and dairy cow health and production. Therefore, the aim of this study was to investigate if there is a connection between the iron content in water and the health of dairy cows. Initially a literature study was made about iron and it´s function in ruminants. The main study was an epidemical investigation evaluating data regarding milk production, disease incidence in dairy cows and water iron analyzes. All data were from dairy farms belonging to "Skånemejerier" (a dairy plant in southern Sweden) between 1997-2003. The statistical analyses showed that there is a significant association between breed and milk production, and between the herd size and the milk production. The disease incidence did also increase with herd size. However, there was no significant effect on iron content in water on disease incidence or milk production.